An Integrated Droplet Manipulation Platform with Photodeformable Microfluidic Channels. Issue 12 (16th November 2021) - Liu, Quan; Yu, Guodong; Zhu, Chongyu; Peng, Bo; Li, Ruohan; Yi, Tao; Yu, Yanlei
Abstract: Manipulating droplets by light in microscale allows precise control of microfluidics, liquid delivery, micromachines, and so on. Among these applications, microfluidic technology is of particular interest for miniaturization of the portable analysis systems, which require the integration of various liquid operations in one device. Here, a photodeformable microfluidic platform is constructed by combining Laplace pressure and capillary condensation to integrate the transportation, fusion, separation, and mixing of liquid slugs in one chip. The Laplace pressure, attributed to the photodeformation of the liquid crystal polymers, is generated to propel the slug. The capillary condensation is introduced by the delicate design of the fluid channels, allowing the fusion and separation of slugs without any connected microvalves. Catalytic oxidation reaction and protein detection processes are realized in the platform, which are amenable to a variety of miniaturized bio‐medical applications, such as portable analysis and point of care testing. Abstract : A photodeformable droplet manipulation platform, in which the transportation, fusion, separation, and mixing of the liquid slugs are integrated in one chip, is fabricated by combining Laplace pressure and capillary condensation. The whole process of bio‐reactions and detections are realized in the platform without any connected pumps and valves, which are amenable to miniaturize the bio‐chemical analysis systems.